2015
DOI: 10.1111/trf.13413
|View full text |Cite
|
Sign up to set email alerts
|

Genotype frequency of human neutrophil antigen‐3 polymorphisms in the Yi, Han, and Tibetan populations of China

Abstract: Background Human neutrophil antigen-3 (HNA-3) alloantibodies can cause fatal transfusion-related acute lung injury (TRALI). Most frequencies of SLC44A2 alleles encoding the HNA-3a/b antigens have been established in Han individuals by PCR-SSP. We sequenced a SLC44A2 gene fragment and determined its allele frequencies in 3 ethnicities of China. Study design and methods Genomic DNA was extracted from 448 samples of 100 blood donors of Yi ethnicity in Xichang, Liangshan; 248 Han in Nanjing, Jiangsu; and 100 Tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Therefore, Northeastern Thais and Burmese may have a higher probability than Karen, potentially forming anti‐HNA‐3a and linking to TRALI. However, the prevalence of the HNA‐3b allele was found to be 0·170–0·239 in Caucasians and 0·026–0·070 in Africans (Chen et al ., ). An estimation of the possible risk of HNA‐3a alloimmunisation in Northeastern Thais, Burmese and Karen showed values of 0·0493, 0·0608 and 0·0196, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, Northeastern Thais and Burmese may have a higher probability than Karen, potentially forming anti‐HNA‐3a and linking to TRALI. However, the prevalence of the HNA‐3b allele was found to be 0·170–0·239 in Caucasians and 0·026–0·070 in Africans (Chen et al ., ). An estimation of the possible risk of HNA‐3a alloimmunisation in Northeastern Thais, Burmese and Karen showed values of 0·0493, 0·0608 and 0·0196, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…However, the newly reported HNA‐3a with 457C > T was not covered by these primer sets. Finally, more recent studies have shown very extensive polymorphisms of the SLC44A2 gene encoding HNA‐3, and the geographical variation of these new alleles and their serological significance and clinical impact remain to be determined (Chen et al, ,b).…”
Section: Discussionmentioning
confidence: 99%
“…We developed a sensitive and specific screening assay to genotype the SLC44A2 gene in a high‐throughput setting. Our decision tree can be applied to any population . A computational approach to predict HNA‐3 antigens from next generation sequencing or WGS data will require a method for detecting carriers of low‐prevalence alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the SNP indicative of the SLC44A2*1 and SLC44A2*2 alleles is known for Caucasian, African American, Han Chinese, Japanese, Tunisian, Brazilian, Thai, and other populations . Chu and colleagues applied an algorithmic approach to predict HNA antigens from whole genome sequencing (WGS) data.…”
mentioning
confidence: 99%